2017
DOI: 10.18632/oncotarget.14580
|View full text |Cite
|
Sign up to set email alerts
|

Gadd45a deficiency accelerates BCR-ABL driven chronic myelogenous leukemia

Abstract: The Gadd45a stress sensor gene is a member in the Gadd45 family of genes that includes Gadd45b & Gadd45g. To investigate the effect of GADD45A in the development of CML, syngeneic wild type lethally irradiated mice were reconstituted with either wild type or Gadd45a null myeloid progenitors transduced with a retroviral vector expressing the 210-kD BCR-ABL fusion oncoprotein. Loss of Gadd45a was observed to accelerate BCR-ABL driven CML resulting in the development of a more aggressive disease, a significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…It is important to note that the human male germ cell line TCam-2 originates from seminoma, which is a type of TGCT [19]. In this context, it is worth noting that almost all NANOS1-repressed pro-apoptotic factors identified in this study (GADD45A, GADD45B, GADD45G, RHOB, and TP53BP2) are well-established tumor suppressors [27][28][29][30][31][32][33][34][35]. This is in line with NANOS1 itself being proposed to promote carcinogenesis [36].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the human male germ cell line TCam-2 originates from seminoma, which is a type of TGCT [19]. In this context, it is worth noting that almost all NANOS1-repressed pro-apoptotic factors identified in this study (GADD45A, GADD45B, GADD45G, RHOB, and TP53BP2) are well-established tumor suppressors [27][28][29][30][31][32][33][34][35]. This is in line with NANOS1 itself being proposed to promote carcinogenesis [36].…”
Section: Discussionmentioning
confidence: 99%
“…Antibody staining was performed on ice for 30 minutes unless specified by the maker. Flow cytometric analysis was carried in a BD FACS Calibur or a BD LSR II flow cytometer as described previously [ 37 ]. Data analysis was performed using FACS Diva (BD Biosciences) or FlowJo software.…”
Section: Methodsmentioning
confidence: 99%
“…BCR-ABL activates multiple signaling pathways including p38MAPK, PI3K/AKT, JNK, STAT5 through its deregulated tyrosine kinase activity to promote proliferation and block differentiation. Our previous study showed that loss of Gadd45a hyperactivated p38MAPK, PI3K/AKT and STAT5 signaling pathways to promote proliferation and reduce apoptosis in BCR-ABL transformed myeloid progenitors [ 14 ]. Thus, it was of interest to determine if the CML suppressive function of Gadd45b is mediated via similar or different signaling pathways.…”
Section: Resultsmentioning
confidence: 99%
“…We have also observed that Gadd45a expression in samples obtained from CML patients was upregulated in more indolent chronic phase CML samples and down regulated in aggressive accelerated phase CML and blast crisis CML [ 14 ]. Thus, studies are underway to determine the expression status of Gadd45b in CML patients.…”
Section: Discussionmentioning
confidence: 99%